Design an air conditioning system for UMP mosque - Mohd Hilmi, Tajud Hassan (2009)
This project is carried out to design a suitable air conditioning system for UMP Mosque. The architectural drawing of UMP mosque is studied first to choose the best air conditioner to be installed in UMP Mosque. Tropical country such as Malaysia is hot and humid. Taking UMP Mosque as an example, during Friday Prayer there is about 1300 Muslims perform Friday Prayer inside UMP Mosque. This situation makes the Muslims feel not comfortable with this condition. Therefore an air conditioning system should be installed in the UMP Mosque to provide comfort to the occupants. The objective of this project is to calculate the heat gains in UMP Mosque. The purpose of calculating the heat gain is to determine the total cooling load required. Another objective is to design a suitable air conditioning system for UMP Mosque. Designing the ductwork, determination of duct size, selection of suitable space to locate the air handling unit (AWl) is done in the design of the air conditioning system. The highest heat gain in UMP Mosque is at 4.00 pm on the daily basis. The total heat gain at 4.00 pm hour is 171.8 W. However, the peak heat gain of 781.4 kW occurs during Friday prayer. Thus, the value of total heat gain during Friday Prayer is used to design the air conditioning system for TJIMP Mosque. The AHUs used are unitary system and each AHU connected with one duct.